Report of Two Cases of Jaw Osteomas - Adarsh Kudva; Ujwal Kumar Malladi; Radhika Singh; Srikanth G (Journal of the California Dental Association, 2025)
Background Osteoma is an osteogenic tumor that is benign in nature and commonly seen in the craniofacial region – commonly classified into three types extraskeletal, central and peripheral. It occurs due to abnormal proliferation of cortical or cancellous bone. The exact etiology is unclear; however, it might occur due to trauma or muscle traction. Peripheral osteoma of mandibular angle is rare. In this paper, we present two cases and review the relevant literature.Case Presentation Two patients present with a swelling of the mandibular angle that gradually increased in size. After utilizing various imaging techniques such as orthopantomography, cone beam computed tomography, 3D computed tomography and correlating clinical and radiological features, peripheral osteoma was diagnosed.Conclusion Surgical resection was performed in both cases with no recurrence reported. Knowledge of peripheral osteoma is essential because if not adequately treated, they can increase in size and cause disfigurement.